C57BL/6J Mouse Apolipoprotein A2 Gene is Deterministic for Apnea - Gillombardo, Carl B. (Respir Physiol Neurobiol, 2016)
RATIONALE: Brainstem apolipoprotein AII (apoa2) mRNA expression correlates with apnea in breathing present in the adult C57Bl/6J (B6) sleep apnea model. OBJECTIVES: To test the hypothesis that the B6 apoa2 gene contributes to the trait, we performed plethysmographic testing in apoa2 knock out (KO: −/−) mice, an in situ brainstem-spinal cord preparation comparing KO to WT (+/+) mice, and B6xDBA recombinant inbred strains (RISs). MEASUREMENTS AND MAIN RESULTS: Apoa2 WT do, but KO and heterozygote (+/−) mice do not exhibit apnea during post-hypoxic breathing, measured in vivo. In the in situ model, pauses and instability in fictive phrenic bursting are substantially reduced in KO vs. WT preparations. In 24 RISs, apnea number in vivo was higher in strains with B6 apoa2 than with DBA apoa2 alleles. CONCLUSIONS: The B6 apoa2 polymorphism is directly involved in breath production, and its identification suggests a novel pathway influencing risk for adult sleep apnea